Gelar Ata (Budak) pada Masyarakat Bulukumba dalam Perspektif Hukum Islam - Muhammad Yusram; Edy Sofyan; Azwar Azwar; Saharuddin Saharuddin (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
This study aims to: (1) describe the description of slavery in Bulukumba; (2) analyze the review of Islamic law against slavery in Bulukumba with the system of awarding the title Ata. This research is a qualitative research using library research and using a normative juridical approach. The results of the study show that: (1) slavery against Ata today is no longer the same as slavery during the kingdom, which was very thick with caste division and slavery. The current system of slavery against Ata is not much anymore and is slowly starting to fade due to the progress and developments of the times, but there are still some people in Bulukumba who apply the system of slavery against Ata because they adhere to customs and think that their slavery is legal because it is a tradition. hereditary; (2) slavery in Bulukumba with the system of giving the title Ata is an act that deprives human rights and freedoms because the essence of Islamic law aims to uphold human rights and equal rights between men and women. Islam does not discriminate against skin color and ethnicity, all are equal before Allah. Therefore, Islam is a religion that does not justify slavery by depriving human rights and freedoms, and doing injustice to others. This is similar to slavery that occurred in the Bulukumba community with the system of giving the nickname or title Ata to certain groups of people, then being enslaved for generations, which is a form of action that is not allowed in Islam.